2017
DOI: 10.1007/s11575-017-0311-5
|View full text |Cite
|
Sign up to set email alerts
|

The Value-Adding Role of the Corporate Headquarters in Innovation Transfer Processes: The Issue of Headquarters Knowledge Situation

Abstract: The aim of this study is to investigate the value-adding role of corporate monitoring and corporate involvement in 'sticky' inter-subsidiary innovation transfer environments. The value added role of these two managerial approaches is viewed in terms of their impact on innovation transfer efficiency and effectiveness. Based on the network view of the MNC, our research builds on the notion that the corporate headquarters (CHQ) is ill-informed and may suffer from a radical uncertainty about what it actually knows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 108 publications
(221 reference statements)
0
2
0
Order By: Relevance
“…The difficulties involved in knowledge transfer were tested at the organizational level to understand how IS occurs (Szulanski, 1996). Prior research (Szulanski, 2000) suggested that the characteristics of the shared best practice are important, in our case, the project's context (Holmström Lind and Kang, 2017). Araujo and Scafuto (2021) argued the need for empirical studies on project management considering the scope of knowledge transfer.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…The difficulties involved in knowledge transfer were tested at the organizational level to understand how IS occurs (Szulanski, 1996). Prior research (Szulanski, 2000) suggested that the characteristics of the shared best practice are important, in our case, the project's context (Holmström Lind and Kang, 2017). Araujo and Scafuto (2021) argued the need for empirical studies on project management considering the scope of knowledge transfer.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Lack of motivation: There is a repulsion of certain receptors to accept external knowledge due to the “not invented here” syndrome (NIH syndrome) (Katz and Allen, 1982). Lack of motivation can lead to a lack of action (Holmström Lind and Kang, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%